2016
DOI: 10.7120/09627286.25.4.447
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability of the Welfare Quality® animal welfare assessment protocol for growing pigs

Abstract: The aim of this study was to assess the feasibility and test-retest reliability of the Welfare Quality® Animal Welfare Assessment Protocol for Growing Pigs. Twenty-three German pig farms were visited repeatedly by the same trained observers; each farm being visited six times during two fattening periods. The entire protocol assessment was carried out during each farm visit, ie a Qualitative Behaviour Assessment (QBA), behavioural observations (BO), a Human Animal Relationship test (HAR) and different individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
32
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 28 publications
8
32
1
Order By: Relevance
“…These results correspond to the results of other studies, e.g. Temple et al (2011) and Czycholl et al (2016b), who confirmed the feasibility of the Welfare Quality Assessment protocol for pigs applied to growing pigs. Czycholl et al (2016b) numbered the time for a complete protocol assessment to 315 min on average ranging from 270 to Table 5.…”
Section: Continuedsupporting
confidence: 91%
See 2 more Smart Citations
“…These results correspond to the results of other studies, e.g. Temple et al (2011) and Czycholl et al (2016b), who confirmed the feasibility of the Welfare Quality Assessment protocol for pigs applied to growing pigs. Czycholl et al (2016b) numbered the time for a complete protocol assessment to 315 min on average ranging from 270 to Table 5.…”
Section: Continuedsupporting
confidence: 91%
“…Temple et al (2011) and Czycholl et al (2016b), who confirmed the feasibility of the Welfare Quality Assessment protocol for pigs applied to growing pigs. Czycholl et al (2016b) numbered the time for a complete protocol assessment to 315 min on average ranging from 270 to Table 5. Mean values (%) and SE of the 5 farm visits (1 to 5) for the scores of the assessment of individual indicators in gestating sows with increased number of animals under assessment Temple et al (2011) executed a complete protocol assessment in 381 min on average ranging from 315 to 580 min.…”
Section: Continuedmentioning
confidence: 67%
See 1 more Smart Citation
“…The PS subjectively evaluates the cattle's willingness to be approached by a human ( Table 3) and may be useful in evaluating the PANIC system. However, the PS has been criticized for lack of objectivity, because different evaluators may have different interpretations of behavior, and several subjective evaluations have suffered from poor inter-rater reliability 26 .…”
Section: Pen Scorementioning
confidence: 99%
“…Thus, not surprisingly, studies concerning the Welfare Quality ® protocols especially have criticised a lack of feasibility, i.e., that an assessment takes too long [ 7 ]. For example, protocol assessments on growing pig farms usually take on average around five hours [ 15 ]. Although the general aim of the Welfare Quality ® project, i.e., that a protocol assessment should be completed within one day, has been reached [ 16 ], this time requirement hinders practical implementation with regard to, e.g., certification purposes or regular self-assessments by the farmers as the question of how to pay for that additional work load remains.…”
Section: Introductionmentioning
confidence: 99%